Fundamentals of Physics / Extended: Fifth Edition - Halliday David; Resnick Robert J; Walker Jearl (John Wiley And Sons, Inc, 1997)
Measurement, Motion Along a Straight Line, Vectors, Motion in Two and Three Dimensions, Force and Motion, Kinetic Energy and Work, Potential Energy and Conservation of Energy, Systems of Particles, Collisions, Rotation, Rolling and Torque and Angular Momentum, Equilibrium and Elasticity, Gravitation, Fluids, Oscillations, Waves, Temperature and Heat and the First Law of Thermodynamics, The Kinetic Theory of Gases, Entropy and the Second Law of Thermodynamics, Electric Charge, Electric Fields, Gauss' Law, Electric Potential, Capacitance, Current and Resistance, Circuits, Magnetic Fields, Magnetic Fields Due to Currents, Induction and Inductance, Magnetism of Matter: Maxwell's Equation, Electromagnetic Oscillations and Alternating Current, Images, Interference, Diffraction, Special Theory of Relativity, Photons and Matter Waves, More about Matter Waves, All about Atoms, Conduction of Electricity in Solids, Nuclear Physics, Energy from the Nucleus, Quarks and Leptons and the Big Bang.